Judicial Pardon: Proyeksi Bunyi Putusan Hakim dalam Perkara Pidana Pasca Undang – Undang Nomor 1 Tahun 2023 Berlaku - Adriyanti, Nadya Fitriza; Zulfa, Eva Achjani (Faculty of Law, Andalas University, 2024)
If the judge determines that the defendant is guilty and has convincingly committed the act in question, but the act does not necessitate punishment based on specific considerations, Article 54, paragraph (2) of Law Number 1 of 2023 concerning the Criminal Code authorizes the judge to grant forgiveness by passing a decision without imposing a penalty. Judge forgiveness, also known as judicial pardon or “rechterlijk pardon”, is one of the sentencing guidelines for judges in deciding criminal cases. Nevertheless, Article 54 paragraph (2) reveals that the factors to be considered by judges in exercising their discretion to grant forgiveness are primarily subjective, with no clear and objective indicators. Furthermore, there are no established guidelines for describing the results of a judge's decision to forgive and structuring the decision. This could lead to a lack of uniformity in judicial pardon decisions when the New Criminal Code comes into force. So, this article attempts to project the sound of the judicial pardon decision using normative legal research. This research indicates that several sentences of the judicial pardon decision can be applied by adopting various criminal choices.